Implications of Islamic Theology on The Psychoanalysis of The Character Ember from The Film Elemental: Forces of Nature - Haryanto, Sri; El Syam, Robingun Suyud; Munawaroh, Hidayatu (International Journal of Islamic Educational Psychology, 2024)
Apart from being an entertainment source, movies can have a deep meaning that benefits life. Some films offer a multidimensional perspective that can be viewed from various aspects. This research explores the psychological condition of Ember, the main character in the film "Elemental: Forces of Nature," through the lens of Sigmund Freud's psychoanalysis and the implications of Islamic theology. The study employs a descriptive qualitative method and analyzes data collected from the film's script and related writings, focusing on Ember's personality and defense mechanisms. At the beginning of the movie, Ember exhibits an unbalanced interplay between her id, ego, and superego, manifesting in her struggle to control her emotions, particularly anger. Freud's psychoanalysis is a comprehensive method but heavily critiqued within Islamic theology for not addressing the aesthetic values of the soul, leading to a perceived dryness. The film portrays Ember as outwardly stable and obedient to her parents, yet internally, she harbors unresolved complaints. Her interaction with Wade, a character embodying the water element who is talkative and enjoys life, aids in stabilizing and enriching her character. The study underscores the Islamic belief that everyone is created in pairs, with diversity as a divine strategy for fostering complementary relationships. The findings highlight the significance of maintaining a balanced lifestyle and adhering to divine guidance for human well-being in the 21st century.